Polyphenol-rich Chinese olive extracts attenuate lipid accumulation in HepG2 cells, accompanied by AMPK phosphorylation and miRNA alterations - Wang, Hong; Huang, Bingqi; Zhao, Wenhong; Liu, Gongliang; Bai, Weidong (Frontiers in Nutrition, 2026)
IntroductionChinese olive (Canarium album L.) is a rich source of phenolic compounds and has been suggested to exhibit distinct lipid-lowering bioactivities from those reported for Mediterranean olive polyphenols.MethodsThis study investigated the effects of polyphenol-rich Chinese olive extracts on sodium oleate-induced lipid accumulation in HepG2 cells.ResultsTreatment with extracts was associated with a significant reduction in intracellular total lipid and triglyceride levels in a concentration-dependent manner. RT-qPCR results revealed that extract treatment was accompanied by the downregulation of lipogenesis-related genes (SREBP-1c, ACC1, FASN, and DGAT2) and the upregulation of β-oxidation-associated genes (PGC-1α, PPARα, CPT-1A, and ACOX1). Western blot analysis showed that extract treatment was associated with AMPK phosphorylation, occurring concurrently with the observed lipid-associated changes. Furthermore, treatment with extracts was accompanied by decreased expression of miR-122 and miR-21, which correlated with the expression of their respective lipid-metabolism target genes. UPLC–MS/MS analysis identified 39 phenolic compounds in the extract, including methyl brevifolincarboxylate and ellagic acid derivatives, indicating a complex phenolic composition.DiscussionThese results demonstrate that attenuation of lipid accumulation by polyphenol-rich Chinese olive extracts in HepG2 cells is accompanied by AMPK phosphorylation and miRNA modulation. This finding supports the potential of Chinese olive extracts as a natural hepatoprotective ingredient for the development of functional foods and nutraceuticals.